Numerical analysis of novel concrete filled K joints with different brace sections - Mampiandra N.H. Zafimandimby; Yongjian Liu; Lei Jiang; Yinping Ma (Heliyon, 2023)
All over the world, truss structures are commonly used in long-span bridge. Since joint is the weakest part of this structure, this paper proposes a novel type in which different brace members are used in the concrete filled box section K-joints. This novel type is designed as rectangular compression brace with the brace width to chord ratio β<0.8 and chord welded tension brace (β=1). That configuration allows to reduce the gap, thus eliminate the secondary moment. Moreover, load transfer and failure modes are not similar to the ordinary. Numerical simulation is the used method of investigation in which validation is carried out through thirty-four models composed of RHS K gap Joint – CFST T Joint – CFST Y Joint – RHS T Integral Joint – CFST K gap Joint. Difference between experiments and Finite Element models are less than 20% thus acceptable. Through the validated numerical simulation model, analysis of suitable boundary conditions and variation of initial stiffness, ultimate strength are presented in accordance with the novel joint parameters. Comparison of the novel joint type to the rectangular hollow section (RHS) and rectangular concrete filled steel tube (RCFST) is carried out in terms of initial stiffness and ultimate strength. Finally, optimization of the novel type of joint is proposed for engineering practice so as to have overview of the strength in practical aspect. Results have shown that most of the proposed types of boundary condition procure the joint deformation while subjected in compression and tension load. Tension brace failure is the typical failure mode of the novel joint in which the chord width, the parameter β are fundamental and directly proportional to the joint initial stiffness and ultimate strength. For β=0.8 and the chord width between 500 and 1000 mm, the initial stiffness can vary from [9944.92kN/mm−19887.31kN/mm]; ultimate strength varies from [29551.76kN−117916.20kN]. Moreover, the novel joint type is stronger than the RHS and the RCFST in both initial stiffness and ultimate strength. That difference is about 3–6% in the initial stiffness and around 10% for the ultimate strength. These demonstrate that the novel type of joint is acceptable in engineering truss bridge with proposition of joint optimization.